Landslide hazard zonation mapping using frequency ratio and relative effect models in Katteri macro watershed Nilgiris district, Tamilnadu. Issue 1 (June 2021) - Rajakumar, C.; Reddybabu, G.; Kodanda Rama Rao, P.
Abstract: Present analysis is endeavored in Kattery macro watershed, Nilgiris District, Tamil Nadu, Republic of India wherever a serious landslide happened. totally different thematic maps relating landslide hazard studies were established from the toposheets and Remote Sensing satellite symbolisms utilizing Geographical system (GIS). Landslide hazard zonation map of Kattery macro watershed was ready by distribution correct weights and ranks for numerous themes. The north eastern and south-western part of Kattery macro watershed is additional susceptible to landslides and also the south-eastern part is a smaller amount vulnerable.